STUDI TAFSIR AL-FURQAN KARYA A. HASAN - Immazaimah; Muhith (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Qur’anic exegesis in Indonesia has developed in response to the socio intellectual and religious dynamics of Muslim society. One significant work in the tradition of Indonesian Qur’anic interpretation is Al-Furqan Tafsir written by A. Hasan, a prominent Islamic reformist scholar known for his rational and purification-oriented approach. This study is motivated by the need to explore the methodological characteristics and interpretive orientation of Al-Furqan Tafsir and its contribution to the development of Qur’anic studies in Indonesia. The purpose of this research is to analyze the background of its composition, the method of interpretation, and the Islamic thought reflected in the tafsir. This study employs a qualitative approach with library research as its main method. The primary data source is Al-Furqan Tafsir, while secondary data are obtained from relevant books and academic articles. Data analysis is conducted through content analysis by examining the structure, interpretive method, and dominant tendencies of interpretation. The findings reveal that Al-Furqan Tafsir applies a tahlili method with a reformist rational orientation, emphasizing the purification of faith, rejection of blind imitation (taqlid), and direct reference to the Qur’an and Hadith. In conclusion, this study affirms that Al-Furqan Tafsir makes a significant contribution to shaping a modern, critical, and contextual tradition of Qur’anic interpretation in Indonesia.